ANALYSIS ON THE STANDARDS OF BRAZILIAN APPLICANTS AVAILABLE IN THE ADOPTION PROCESS - Faleiro, Júlia; Souza, Eliane Eliane de Franà§a (CIPEEX, 2022)
IT WAS UNDERSTOOD THAT THE CRITERIA OF AVAILABLE SUITORS REGISTERED IN THE NATIONAL ADOPTION AND FOSTERING SYSTEM (SNA) IN BRAZIL HAS A WELL-DEFINED PATTERN. CURRENTLY, STILL ACCORDING TO THE SNA (2021), THERE ARE 32.831 CANDIDATES FOR ADOPTION IN BRAZIL AND 4.263 AVAILABLE CHILDREN. SO, IF THERE ARE ALMOST 8 APPLICANTS FOR EVERY 1 CHILD, WHY HAVEN'T THEY ALL BEEN ADOPTED YET? THE GENERAL OBJECTIVE IS TO ANALYZE THE CRITERIA ADOPTED TO CHOOSE THE APPLICANTS REGISTERED IN THE SNA AND THE REASONS FOR THE NON-ADOPTION. TO REACH THE EXPECTED RESULTS, THE FOLLOWING SPECIFIC OBJECTIVES WERE DEFINED: A) DEFINE THE STANDARDS IMPOSED BY THE APPLICANTS; B) ANALYZE THE PROFILES OF THE AVAILABLE CHILDREN; C) DISCUSS THE NUMERICAL IMBALANCE BETWEEN APPLICANTS AND AVAILABLE CHILDREN. STILL ACCORDING TO THE SNA, AMONG THE 32,831 APPLICANTS FOR ADOPTION, ONLY 4 WANT TO ADOPT TEENAGERS UP TO OR OVER 15 YEARS OLD, WHILE OF THE 4,263 AVAILABLE CHILDREN, MORE THAN 1,000 ARE UP TO OR OVER 15 YEARS OLD. THE WAY OUT WOULD BE NOT TO LET THE APPLICANTS CHOOSE A STANDARD CHILD TO ADOPT, BUT TO LET THE CHILDREN CHOOSE WHICH FAMILY TO STAY WITH, AND THE APPLICANTS WHO HAVE DECIDED TO ADOPT ARE ALREADY AWARE THAT THEY HAVE NOT CHOSEN THE CHILD, NOR HIS OR HER AGE OR COLOR.